The Use of Wordwall in Vocabulary Selection in Narrative Texts of Students in Class VII-1 SMP Palangka Raya - Perdana, Indra; Bungai, Joni; Oscar, Scherschligt; Kathryn, Morse (Journal International Inspire Education Technology, 2023)
Learning media is one of the important factors that influence learning outcomes. The selection and use of appropriate and interesting media will have a good impact on student learning success. The use of technology-based learning media is still not widely done at SMPN 2 Palangka Raya. This study aims to apply Wordwall media as a medium for doing assignments and helping students in choosing the right vocabulary in the Imagination story. This research was conducted on students of class VII-I. Procedure for collecting data through observation, documentation, pre-test, post-test and interviews. Data were analyzed through data reduction, data presentation and drawing conclusions. The results showed that the application of Wordwall media can help students in working on the task of choosing Vocabulary in the Imagination story. It can be seen from the change in the score between the Pre Test and Post Test which has increased.